Ca(2+)/calmodulin-activated phosphodiesterase 1A is highly expressed in rabbit cardiac sinoatrial nodal cells and regulates pacemaker function - Lukyanenko, Yevgeniya O; Younes, Antoine; Lyashkov, Alexey E; Tarasov, Kirill V; Riordon, Daniel R; Lee, Joonho; Sirenko, Syevda G; Kobrinsky, Evgeny; Ziman, Bruce; Tarasova, Yelena S; Juhaszova, Magdalena; Sollott, Steven J; et al. (Journal of molecular and cellular cardiology, 2016)
Constitutive Ca(2+)/calmodulin (CaM)-activation of adenylyl cyclases (ACs) types 1 and 8 in sinoatrial nodal cells (SANC) generates cAMP within lipid-raft-rich microdomains to initiate cAMP-protein kinase A (PKA) signaling, that regulates basal state rhythmic action potential firing of these cells. Mounting evidence in other cell types points to a balance between Ca(2+)-activated counteracting enzymes, ACs and phosphodiesterases (PDEs) within these cells. We hypothesized that the expression and activity of Ca(2+)/CaM-activated PDE Type 1A is higher in SANC than in other cardiac cell types. We found that PDE1A protein expression was 5-fold higher in sinoatrial nodal tissue than in left ventricle, and its mRNA expression was 12-fold greater in the corresponding isolated cells. PDE1 activity (nimodipine-sensitive) accounted for 39% of the total PDE activity in SANC lysates, compared to only 4% in left ventricular cardiomyocytes (LVC). Additionally, total PDE activity in SANC lysates was lowest (10%) in lipid-raft-rich and highest (76%) in lipid-raft-poor fractions (equilibrium sedimentation on a sucrose density gradient). In intact cells PDE1A immunolabeling was not localized to the cell surface membrane (structured illumination microscopy imaging), but located approximately within about 150nm inside of immunolabeling of hyperpolarization-activated cyclic nucleotide-gated potassium channels (HCN4), which reside within lipid-raft-rich microenvironments. In permeabilized SANC, in which surface membrane ion channels are not functional, nimodipine increased spontaneous SR Ca(2+) cycling. PDE1A mRNA silencing in HL-1 cells increased the spontaneous beating rate, reduced the cAMP, and increased cGMP levels in response to IBMX, a broad spectrum PDE inhibitor (detected via fluorescence resonance energy transfer microscopy). We conclude that signaling via cAMP generated by Ca(2+)/CaM-activated AC in SANC lipid raft domains is limited by cAMP degradation by Ca(2+)/CaM-activated PDE1A in non-lipid raft domains. This suggests that local gradients of [Ca(2+)]-CaM or different AC and PDE1A affinity regulate both cAMP production and its degradation, and this balance determines the intensity of Ca(2+)-AC-cAMP-PKA signaling that drives SANC pacemaker function.